A comparative analysis of European and American eel ( Anguilla anguilla and Anguilla rostrata) genomic DNA: 5S rDNA polymorphism permits the distinction between the two populations - Nieddu, M; Pichiri, G; Coni, P; Salvadori, S; Deiana, A M; Mezzanotte, R (Genome, 1998)
We studied possible molecular and cytological correlations between the European (Anguilla anguilla) and the American (Anguilla rostrata) eel, using either low molecular weight highly repetitive sequences isolated from genomic DNA of the two species, or highly conserved sequences, such as 45S or 5S rDNA, as probes. A clearcut difference was found only in filter hybridization experiments carried out using 5S rDNA as probe.Key words: fish, chromosomes, DNA, endonucleases, rDNA.